Employee suggestion systems : boosting production and profits - Bassford, Robert L. (Crisp Pub. Menlo ParkUS, 1996)
Deals with benefits of an Employee Suggestion System (ESS); explains how to set it up; discusses promotion ideas for it; and, presents suggestions for avoiding problems with it.